2016
DOI: 10.12957/jse.2016.23707
|View full text |Cite
|
Sign up to set email alerts
|

Metal Sorption by Sediments From a Mangrove Reforestation Area in Guanabara Bay (Se Brazil) Revealed by Using Radiotracers

Abstract: This work applied the radiotracer technique to evaluate the chromium (Cr) sorption by sediments of a mangrove degraded area under reforestation phase. The radiotracer 51 Cr(III) was used to assess the removal kinetics of this metal from tidal water by underlying sediments in two different environments from the mangrove area of the reserve Parque Natural Municipal Barão de Mauá (Rio de Janeiro, SE Brazil). The results indicated a faster Cr(III) removal by sediments from the area with initial mangrove reforestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is therefore used as a reference for the standardization of other isotopes of this element 2016; Laut et al, 2016Laut et al, , 2019Dias et al, 2017;Alves Martins et al, 2018;Pregnolato et al, 2018). These materials have great affinity to heavy metals (Alves Martins 2015;Martins et al, 2015Martins et al, , 2017Suzuki et al, 2016;Zaaboub et al, 2016;Díaz Morales et al, 2019b) and can provide temporal information regarding the beginning of anthropic influence in the environment (Vilela et al, 2014;Bueno et al, 2019), which is one of the objectives of this research. Ferrand et al (1999), analyzing stable isotopes of lead in 24 cores (0-50 cm) of several transects in the Gulf of Lion (France), observed that lead concentrations (23-85 ppm) and isotopic signatures 206 Pb/ 207 Pb (1.174 -1.188) in the surface sediments, clearly evidenced the impact of polluting lead, which contributed for 22-80% of the lead accumulated in the first centimeter of the sediments in the studied sites.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore used as a reference for the standardization of other isotopes of this element 2016; Laut et al, 2016Laut et al, , 2019Dias et al, 2017;Alves Martins et al, 2018;Pregnolato et al, 2018). These materials have great affinity to heavy metals (Alves Martins 2015;Martins et al, 2015Martins et al, , 2017Suzuki et al, 2016;Zaaboub et al, 2016;Díaz Morales et al, 2019b) and can provide temporal information regarding the beginning of anthropic influence in the environment (Vilela et al, 2014;Bueno et al, 2019), which is one of the objectives of this research. Ferrand et al (1999), analyzing stable isotopes of lead in 24 cores (0-50 cm) of several transects in the Gulf of Lion (France), observed that lead concentrations (23-85 ppm) and isotopic signatures 206 Pb/ 207 Pb (1.174 -1.188) in the surface sediments, clearly evidenced the impact of polluting lead, which contributed for 22-80% of the lead accumulated in the first centimeter of the sediments in the studied sites.…”
Section: Introductionmentioning
confidence: 99%